Beyond Networks: Health, Crime, and Migration in Mexico. (24th July 2014) - Martinez, Jose N.
Abstract : Two rounds of a longitudinal survey from Mexico, representative at the national, urban, rural, and regional level, are used to examine the determinants of local, domestic, and international migration. Aside from the typical covariates in the migration decision, this study considers health conditions, crime, and individual's perspectives on life as explanatory variables. Coefficient estimates for most health variables do not offer significant support to the healthy migrant hypothesis. In terms of crime, the results suggest that females respond to worsening safety conditions in Mexico by migrating domestically, but not abroad. The decision to migrate domestically or abroad for males is not statistically correlated with increases in crime. Overall, having access to international migration networks continues to play a significant role in the decision to migrate to the US.